Branched Polyethylenimine-Superparamagnetic Iron Oxide Nanoparticles (bPEI-SPIONs) Improve the Immunogenicity of Tumor Antigens and Enhance Th1 Polarization of Dendritic Cells. (28th June 2015) - Hoang, My-Dung; Lee, Hwa-Jeong; Lee, Hyun-Ju; Jung, Sung-Hoon; Choi, Nu-Ri; Vo, Manh-Cuong; Nguyen-Pham, Thanh-Nhan; Kim, Hyeoung-Joon; Park, In-Kyu; Lee, Je-Jung
Abstract : Nanoparticles in the field of dendritic cell (DC) research are emerging as a promising method of enhancing the efficacy of cancer immunotherapy. We investigated the effect of branched polyethylenimine-superparamagnetic iron oxide nanoparticles (bPEI-SPIONs) on tumor cells loaded onto DCs. The tumor antigens were prepared as follows: (1) apoptotic U266 cells with ultraviolet B (UVB) irradiation followed by a 2 h incubation in the absence (2 h postirradiated cells) or (2) presence of bPEI-SPIONs (bPEI-SPION 2 h postirradiated cells) and (3) apoptotic U266 cells with UVB irradiation followed by an overnight 16 h incubation (16 h postirradiated cells). bPEI-SPIONs render U266 cells sensitive to UVB irradiation through reactive oxygen species production to accelerate apoptotic death. The 2 h postirradiated cells and bPEI-SPION 2 h postirradiated cells released immunogenic proteins, including Hsp70, Hsp90, and HMGB1. The DCs loaded with bPEI-SPION 2 h postirradiated cells showed the highest IL-12p70 production and Th1 polarization compared with other DCs. These results suggest that bPEI-SPIONs are a promising method of enhancing the immunogenicity of tumor cells and promoting Th1 polarization of DCs loaded with these tumor cells.